2014
DOI: 10.1002/sca.21171
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of various irrigation activation protocols and the self-adjusting file system on smear layer and debris removal

Abstract: The purpose of the present study is to evaluate smear layer generation and residual debris after using self-adjusting file (SAF) or rotary instrumentation and to compare the debris and smear layer removal efficacy of the SAF cleaning/shaping irrigation system against final agitation techniques. One hundred and eight maxillary lateral incisor teeth were randomly divided into nine experimental groups (n = 12), and root canals were prepared using ProTaper Universal rotary files, with the exception of the SAF inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 36 publications
1
19
1
3
Order By: Relevance
“…G2, G5, and G6 showed no significant difference among their scores. Similar to the others studies (Andrabi et al, ; Castagna et al, ) the agitation of the EDTA solution with ultrasound did not increase the efficiency of smear layer removal, but other authors found different results (Arslan et al, ; Capar & Aydinbelge, ; Kuah et al, ). The different results found may be related to the use of human teeth and the modeling of the canal of instruments with smaller diameter.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…G2, G5, and G6 showed no significant difference among their scores. Similar to the others studies (Andrabi et al, ; Castagna et al, ) the agitation of the EDTA solution with ultrasound did not increase the efficiency of smear layer removal, but other authors found different results (Arslan et al, ; Capar & Aydinbelge, ; Kuah et al, ). The different results found may be related to the use of human teeth and the modeling of the canal of instruments with smaller diameter.…”
Section: Discussionsupporting
confidence: 82%
“…A lower volume of at prepared root canal hinders the diffusion of irrigating solution throughout its interior during conventional irrigation. The use of an ultrasonic tip improves the irrigating solutiońs contact with all walls of the root (Capar & Aydinbelge, ; Castagna et al, ; Kuah et al, ) and the higher scores in samples with the ultrasonic irrigation of the sodium hypochlorite solution (G4) suggest that the mechanical action of this agitation can cause the formation of a smear layer. The present study did not assess the action of irrigation solutions in areas of anatomical complexity such as the isthmus and grooves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different techniques have been proposed to improve irrigant distribution within the root canal system (Çapar & Aydinbelge, , Lee, Wu, & Wesselink, , Saber Sel & Hashem, ). Passive ultrasonic irrigation (PUI) is a non‐invasive irrigation protocol applied with ultrasonically activated files, and could be used with a continuous or intermittent flow of irrigant (Van Der Sluis, Wu, & Wesselink, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Frente a esses achados e aos diversos novos mé-todos coadjuvantes de agitação da irrigação, recomenda-se a agitação do EDTA, por um minuto, seguido da agitação do NaOCl, para a remoção efetiva de ambos os componentes, orgânicos e inorgânicos, da camada de smear layer após o preparo biomecâ-nico dos canais radiculares, o que permite uma adequada desinfecção do SCR, sem no entanto alterar a estrutura dentinária 63,64 . Uma nova proposta de ativação do EDTA, por meio da utilização de LASER de baixa potência, também foi avaliada 27,58,[65][66][67][68][69] .…”
Section: Discussionunclassified